Mapping Indigenous Knowledge in Science Education: A Systematic Literature Network and Bibliometric Analysis - Kurdiati, Lintang Auliya; Susiloningsih, Esti; Fathurohman, Apit (Universitas Negeri Makassar, 2025)
This study aims to map and synthesize research on the integration of indigenous knowledge in science education published between 2015 and 2025. A systematic literature network analysis (SLNA) was employed by combining PRISMA-guided screening with bibliometric and science mapping techniques. Data were retrieved from the Scopus database, yielding 667 initial records that were refined through duplicate removal, title and abstract screening, and full-text eligibility assessment based on predefined criteria. This process resulted in a final corpus of 56 core articles. Biblioshiny and VOSviewer were used to analyze publication trends, citation relationships, thematic structures, and bibliographic coupling patterns. The findings indicate a consistent growth in research output, largely concentrated in Anglophone countries, with emerging cross-regional collaboration. Three dominant research streams were identified: curriculum contextualization, environmental sustainability, and culturally sustaining pedagogies. Bibliographic coupling further reveals a distinction between established theoretical frameworks and emerging pedagogical and epistemological approaches. The study concludes that indigenous knowledge integration in science education represents a rapidly evolving research field and provides a systematic conceptual mapping to support more inclusive, context-sensitive, and epistemically plural science learning.